Pathology of Hereditary Breast and Ovarian Cancer - Hodgson, Anjelica; Turashvili, Gulisa (Frontiers in Oncology, 2020)
Hereditary breast and ovarian cancer (HBOC) syndrome is most commonly characterized by deleterious germline mutations in BRCA1 and BRCA2. HBOC patients are prone to the development of malignant neoplasms in multiple organs including the breast, ovary, and fallopian tube. From a pathological perspective, a number of morphological features have been described in BRCA-associated breast and tubo-ovarian cancers. For example, breast cancers diagnosed in BRCA1-mutation carriers are frequently of a high Nottingham grade and display medullary morphology and a triple-negative and/or a basal-like immunophenotype. In contrast, breast cancers in BRCA2-mutation carriers are similar to sporadic luminal-type tumors that are positive for hormone receptors and lack expression of human epidermal growth factor receptor 2. Cancers arising in the fallopian tube and ovary are almost exclusively of a high-grade serous histotype with frequent Solid, pseudoEndometrioid, and Transitional cell carcinoma-like morphology (“SET features”), marked nuclear atypia, high mitotic index, abundant tumor infiltrating lymphocytes, and necrosis. In addition, pushing or infiltrative micropapillary patterns of invasion have been described in BRCA-associated metastases of tubo-ovarian high-grade serous carcinomas. Besides BRCA1 and BRCA2 mutations, alterations in a number of other homologous recombination genes with moderate penetrance, including PALB2, RAD51C, RAD51D, BRIP1 and others, have also been described in HBOC patients with varying frequency; however, distinct morphological characteristics of these tumors have not been well characterized to date. In this review, the above features are discussed and a focus is placed on how accurate pathologic interpretation plays an important role in helping HBOC patients receive the best possible management.